Pedagogical challenges in folk music teaching in higher education: a case study of Hua'er music in China. Issue 1 (11th January 2016) - Yang, Yang; Welch, Graham
Abstract : Recent literature suggests that traditional approaches in folk music education are not necessarily compatible with the pedagogical conventions of formal music education. Whilst several recent studies have tended to define these non-classical-music learning contexts as 'informal', the practice of folk music that was recently introduced into Chinese Higher Music Education appears to be much more complex and fluid, at least in its real world setting. This case study presents a detailed example of the teaching and learning of folk singing in contemporary society in Western China. In this particular context, both 'informal learning' and 'formal' music practices were observed and compared, based on research data collected from four music lessons and subsequent interviews with the participants. Drawing upon the analytical evidence, the research discusses a possible pedagogical model where two apparently contrasting approaches to learning (i.e. a conservatory model vs. traditional folk learning) could coalesce to ensure more effective learning outcomes of traditional folk music in higher education contexts.